(3MGhi GdMSGf ef MjGI GdMjhGfs - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s; (3GdOejQj , ceGd GdOjf CHh GdHbGA eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj, GdOejQj,J (B808 (3g` s ((3eMeO Hf ZGRi GdOefeghQi s)
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ eMeO Hf YHO GdbGOQ Hf eMeO GdOejQi GdMfai Ef cJGH MjGg GdMjhGf GdcHQi s
(3BNQgG (B:s
(3Mceg JMQje GdCcd efaQOkG dCfg fhY ef GdOhO hGddg CYde Je GdLRA GdChd ef MGhi GdMSGf ef MjGI GdMjhGf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs